The message of Acts to the ends of the earth - Stott, John Robert Walmsley, 1921- (Leicester, UK IVP, 1990)
Includes bibliographical references.
"The Bible speaks today" series has been placed in the library in memory of Gordon W. Craig, 1926-1990
Keywords: Bible. N.T. Acts -- commentaries